Optimum oil palm shell content as coarse aggregate in concrete based on mechanical and drying shrinkage properties / Mehdi Maghfouri - Mehdi, Maghfouri (2019)
Oil palm shell (OPS) is a bio-solid waste in palm oil industry in tropical region which could be used as aggregate in concrete mixture. For more than three decades, OPS has been experimented as lightweight aggregate to produce lightweight aggregate concrete (LWAC). The use of this solid waste is not only a practical way to reduce the negative impact of the construction industry but also leads to a low-cost material. Medium and high strength LWAC using of OPS as coarse aggregate was successfully produced and reported by the researchers. However, high drying shrinkage at early and later ages is considered as a drawback for this type of concrete. From previous studies it was concluded that increasing the volume of OPS in concrete mixtures, leads to lower mechanical properties and higher drying shrinkage. In this regard, comprehensive experimental study was carried out to investigate the effect of partial replacement of crushed granite aggregates in normal-weight concrete (NWC) with OPS on mechanical properties and drying shrinkage behaviour in order to obtain the optimum level of OPS contribution in concrete mixture. For this study, six concrete mixes were designed using crushed granite and the OPS as coarse aggregates. The NWC by using of crushed granite aggregate and density of 2340 kg/m3 was considered as control concrete, and for all other mixes, crushed granite was partially replaced with OPS from 0 to 100% (by volume) with interval of 20% and a constant water to cement ratio of 0.33. The influence of curing condition on mechanical properties and drying shrinkage of concretes was also considered. Three different conditions of curing, namely, air curing (AC) to simulate the practical curing condition, 28 days’ water curing (28D) and 7 days curing in water and then air drying (7D) in the laboratory environment, are employed to examine 28-day compressive strength. The results of the study clearly indicated that up to 60% replacement of crushed granite aggregates by OPS in NWC, structural lightweight aggregate concrete with maximum drying shrinkage strain of approximately 500 micro-strain can be produced which is in allowable limit for drying shrinkage. Whereas in long-term ages (275 days) the value of drying shrinkage was 33% higher than the control mix. For mixes containing OPS beyond 60% the increment of shrinkage was significantly higher. Furthermore, for mixes containing up to 60% OPS, mechanical properties and final water absorption were satisfactory.